Pengujian Kualitas Air Sumur Bor di Kelurahan Anaiwoi Dengan Menggunakan Parameter pH Dan TDS - Muhammad Buttomi Masgode; Retno Puspaningtyas; Fathur Rahman Rustan; Arman Hidayat; Bagus Eko Prasetyo; Mursalim Ninoy La Ola; Al Tafakur La Ode; Mansyur Mansyur; Haerul Purnama; Arya Dirgantara; Rina Rembah; Sahrul Poalahi Salu; Arif Arif; Syahrul Syahrul; Nurfasiha Nurfasiha; Hasriyanti Hasriyanti; Isramyano Yatjong; La Ode Dzakir; Rizki Kumalasari; Suwarto Suwarto (ANOA: JURNAL PENGABDIAN MASYARAKAT FAKULTAS TEKNIK, 2023)
Water is a natural resource that is crucial for the survival of all living beings, including humans. The quality of water is an important factor that can have a significant impact on human health. To ensure the well-being of the community, water quality testing was conducted at 2 drilled wells that are being used by residents of Anaiwoi Village. Based on the water quality testing results, it was found that the pH value at point 1 was between 4,6-4,8, while at point 2, it was between 4.6 - 5.9. Unfortunately, the pH values at both points were below the Environmental Health Quality Standards. On the other hand, the Total Dissolved Solid (TDS) parameters at both points were found to be within the Environmental Health Quality Standards. This is because the TDS values obtained were less than 300 mg/L or less than 300 ppm.